How Does Independent Practice of Multiple-Criteria Text Influence the Reading Performance and Development of Second Graders?. (February 2014) - Cheatham, Jennifer P.; Allor, Jill H.; Roberts, J. Kyle
This study examined the impact of independent practice of multiple-criteria text that targeted high-frequency words, decodability, and meaningfulness. Second-grade students, including at-risk students, were randomly assigned within classroom to a treatment group that read multiple-criteria text ( n = 34), or contrast group that read authentic literature (i.e., children's books without intentionally imbedded scaffolds; n = 28) during daily 30-min independent reading sessions for 10 weeks. Pre–post data analysis indicated no statistically significant group differences, though a moderate effect size of .67 was found for the word reading of developing decoders in the treatment group. HLM analyses also provided preliminary evidence that practice with multiple-criteria text may be more effective than practice with authentic literature for developing decoders but not advanced decoders.